Rural Electrification Through Decentralised Off-grid Systems in Developing Countries - Bhattacharyya, Subhes (Green Energy and Technology, 2013)
More than 1.3 billion people worldwide lack access to electricity. Although extension of the electricity grid remains the preferred mode of electrification, off-grid electrification can offer a solution to such cases. Rural Electrification through Decentralised Off-grid Systems in Developing Countries provides a review of  rural electrification experiences with an emphasis on off-grid electrification and presents business-related aspects including participatory arrangements, financing, and regulatory governance.   Organized in three parts, Rural Electrification through Decentralised Off-grid Systems in Developing Countries  provides comprehensive coverage and state-of-the art reviews which appraise the reader of the latest trend in the thinking. The first part presents the background information on electricity access, discusses the developmental implications of lack of electricity infrastructure and provides a review of alternative off-grid technologies. The second part presents a review of experiences from various regions (South Asia, China, Africa, South East Asia and South America). Finally, the third part deals with business dimensions and covers participatory business models, funding challenges for electrification and regulatory and governance issues.   Based on the research carried out under the EPSRC/ DfID funded research grant for off-grid electrification in South Asia, Rural Electrification through Decentralised Off-grid Systems in Developing Countries provides a multi-disciplinary perspective of the rural electrification challenge through off-grid systems. Providing a practical introduction for students, this is also a key reference for engineers and governing bodies working with off-grid electrification.